The Many Meanings of Evidence: Implications for the Translational Science Agenda in Healthcare - Gill Harvey (Kerman University of Medical Sciences, 2013)
Health systems across the world are concerned with the quality and safety of patient care. This includes investing in research and development to progress advances in the treatment and management of individuals and healthcare organisations. The concept of evidence- based healthcare has gained increasing currency over the last two decades; yet questions persist about the time it takes for new research evidence to find its way into day to day healthcare decision-making. This paper explores the reasons for this apparent gap between research and healthcare practice, management and policy-making. In particular, the paper argues that different meanings attached to the word 'evidence' fundamentally influence the way in which the research-practice gap is conceptualised and subsequent strategies that are implemented to increase the uptake of research.